UML Based Approach Toolkit to Model Object Behaviour in a Simulation Environment - Damian FRĄSZCZAK (Communications of International Proceedings, 2021)
Traditionally simulation experiments require expert knowledge to transform domain-specific behaviours into simulation engine code. The proposed solution allows replacing that approach with a more automatic one based on UML activity diagrams to model the high-level behavioural model and then transform it into an executable artefact that can be easily embedded in various simulation engines.
Keywords: Simulation; Behavioural Modelling; Code Generation